Effects of inorganic nutrient enrichment on the carrageenan yield, growth, and ice-ice disease occurrence of red alga Kappaphycus striatus - Sarri, Jurmin H.; Abdulmutalib, Yusop A.; Mohammad Tilka, Melapearl E.; Terzi, Ertuğrul; Tahiluddin, Albaris B. (Scientific Web Journals (SWJ), 2022)
One of the problems in Kappaphycus farming is the slow growth in some farms due to nutrient insufficiency caused by overstocking. In the southern Philippines, most seaweed farmers practice inorganic nutrient enrichment of Kappaphycus to boost growth and decrease ice-ice disease occurrence using ammonium phosphate at an average concentration of 8.82 g L-1. In this study, experiments with Kappaphycus striatus enriched with inorganic nutrients were carried out at Pasiagan, Bongao, Tawi-Tawi, southern Philippines, using different inorganic nutrients (T1=8.82 g L-1 of urea, T2=8.82 g L-1 of phosphorus, and T3=control) within 45 days. Seaweeds were enriched in these three inorganic solutions for 30 seconds, placed into a large mat, covered with canvas, and left overnight. After 15 days, findings showed that the specific growth rates of T1 (6.99% day-1) and T3 (6.72% day-1) groups were significantly higher than the T2 (5.84% day-1) group (p<0.05). Inorganic nutrient enrichment did not significantly influence the occurrence of ice-ice disease. Moreover, inorganic nutrient enrichment did not affect the carrageenan yield after 45 days. K. striatus nutrient-enriched with urea could increase growth at day 15, but no effect on the occurrence of ice-ice disease and carrageenan yield. Hence, inorganic nutrient enrichment using urea provides a positive effect to farmed K. striatus by enhancing its growth without affecting its health and carrageenan yield.
Keywords: Maritime Engineering (Other); Carrageenan yield; Ice-ice disease; Kappaphycus striatus; Nutrient enrichment; Specific growth rate; Deniz Mühendisliği (Diğer); 2. Zero hunger; 6. Clean water